Instruments of Mass Destruction - Slovene Model of Systematic Protection (Kriminalističke teme, 2004)
In the event of threats or attacks with instruments or weapons of mass destruction it is necessary to carefully plan and establish a systematic solution to avert these kinds of threats. Past experiences have shown, that police, who are readily prepared, qualified and equipped with protection before attacks of this nature, also expertly and efficiently sohe, other similar cases (For example, attacks with explosive devices with potential for a large explosion and extensive damage).On the basis of concrete examples in the Republic of Slovenia it is possible for one to conclude, that in the Republic of Slovenia there is an absence of systematic regulations in the area of instruments or weapons of mass destruction ivhich is cause for concern. A number of state organs and other institutions have protective regulations in the case of a threat or attack. However concrete examples have shown that failure to have systematic regulations in place means late and ineffective measures for individual state organs. The police, respectively the working organization, after all their hard work and warning to the government of the Republic of Slovenia, have attained the founding of a national coordination committee with a working organization dealing with threats and attacks with instruments or weapons of mass destruction.